Archive Fever di Okwui Enwezor (2008): nuove fonti per l’analisi di una mostra di successo - Gitto, Fabrizio (Rivista di studi di fotografia. Journal of Studies in Photography, 2019)
Despite its success, the 2008 exhibition Archive Fever. Uses of the Document in Contemporary Art curated by Okwui Enwezor at the International Center of Photography in New York has never been subjected to close examination. The aim of this essay is to reconsider the exhibition’s rationale in relation to previous debates on the notion of the archive and on archival art, and to analyze Enwezor’s curatorial choices in terms of artworks and their installation.